Development of Battery Energy Management System for EV Charging Station - Dineshraj, V.; Moorthy, V. Prasanna (Journal of Soft Computing Paradigm, 2022)
Designing energy storage technologies for applications such as power and smart grids has become a need in the last era, and it is heavily reliant on accurate battery conditions as well as characteristic predictions. A variety of techniques are used to identify battery properties and describe battery states, depending on the kind of battery cell and how it is utilized. This study focuses on estimating the State of Charge (SOC), which is one of the most critical battery states. The most significant aspect of batteries is their State of Charge, which represents their accuracy and state. For charging and discharging, the Coulomb-counting approach is used in mathematical modeling to determine the battery’s SOC. The proposed system maintains the SOC of the battery when it undergoes deep outflow in the input ports that exceeds its limitation during the charging of EVs in electric vehicle charging stations. Simulations utilizing MATLAB/ Simulink software are used to assess the suggested method’s performance.